Detection of Subsurface Voids in Soil Media Using Seismic Wave Methods - A. Srivastava; J. A. Laman; A. Schokker (Global Journal of Earth Science and Engineering, 2016)
This research investigated the effect of anomalies such as voids on surface wave propagation. This was achieved by studying the signal simultaneously in both the time and frequency domains with the assistance of time-frequency plots generated by continuous wavelet transformation (CWT). The study also investigated the effects of different types of wavelets on CWT and developed a protocol for processing seismic wave data for void detection. For this purpose a numerical and experimental study was conducted and the data was studied in both the time and frequency domains in conjunction with time-frequency plots. The response of the soil media is presented in the time-frequency plots. The presence of void like anomalies disrupts the time-frequency plot features and introduces new features. These features have been used for cavity detection.